Monkeypox in Pakistan-First case report - Nasim Akhtar (Journal of the Pakistan Medical Association)
Monkeypox (mpox) is an uncommon zoonotic contagious viral ailment, resulting from the poxvirus. Symptoms include fever, headache, muscle aches, and a characteristic rash. There is no specific treatment, and only a limited number of antiviral drugs and vaccines are available. Employing stringent contact and respiratory precautions is essential to curb disease transmission.